A Framework for Selecting and Implementing Ground Mobile Inspection Robots in Industrial Applications - Silveira, Filipe; Gago, Reynaldo Mateus; Moura, Ralf Luis De; Freitas, Gustavo Medeiros (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
The utilization of ground mobile inspection robots in industrial applications has gained significant traction due to their ability to enhance safety, efficiency, and data accuracy in hazardous environments. This paper introduces a framework designed to assist in selecting and implementing these robots in industrial setting, addressing the critical need for choosing the most suitable for specific inspection tasks. The framework categorizes critical capabilities into several key domains including navigation, inspection, integration, constructive characteristics and support. Then, this paper evaluates nine robots based on those domains, revealing significant variances in their capabilities, and establishes a workflow for selecting the most suitable robots to address the specific needs of different inspection tasks. This paper concludes that the adoption of this framework and workflow may guide industries in making informed decisions about integrating inspection robots, thereby improving operational safety, reducing risks, and enhancing inspection efficiency.